2010
DOI: 10.3109/09513590.2010.526658
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the TSHRc-Asp727Glu polymorphism and plasma thyroid stimulating hormone levels in Romanian preeclamptic women

Abstract: Higher TSH levels and/or the TSHRc-Asp727Glu polymorphism represent risk factors for preeclampsia and could be correlated with the severity of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Maternal age is one of the essential risk factors in women with Preeclampsia. The risk of pre-eclampsia is higher when the age of pregnant women is less than 25 years [11] In the present study, the majority of the patients selected in both the groups were in the age group of 21-25 years, which comprising 50% in the control group and 50% in the preeclampsia group. However, this study shown blood pressure variation in the normotensive group was 75.60 ± 5.77 and in preeclampsia group was 101.40±10.50.…”
Section: Resultsmentioning
confidence: 52%
“…Maternal age is one of the essential risk factors in women with Preeclampsia. The risk of pre-eclampsia is higher when the age of pregnant women is less than 25 years [11] In the present study, the majority of the patients selected in both the groups were in the age group of 21-25 years, which comprising 50% in the control group and 50% in the preeclampsia group. However, this study shown blood pressure variation in the normotensive group was 75.60 ± 5.77 and in preeclampsia group was 101.40±10.50.…”
Section: Resultsmentioning
confidence: 52%
“…The TSHR-Glu727 variant has been proposed to have higher activity than the wild-type variant because less TSH is required to maintain normal serum free thyroxine (FT 4 ) levels (19,20,21), indicating higher sensitivity of the receptor. Previous reports have assessed the effect of the TSHR-Asp727Glu polymorphism on various clinical outcomes, including bone metabolism, glucose metabolism, and preeclampsia (21,22,23,24). Furthermore, a TSHR-mediated mechanism was proposed to be involved in stimulation of type 2 iodothyronine deiodinase (D2) expression in various tissues (7,8,15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, preeclampsia may also predispose to the development of hypothyroidism in later years after delivery [ 15 ]. It also has been suggested that attention should be paid to the monitoring of thyroid function in pregnant women with preeclampsia because of the higher risk of hypothyroidism [ 16 ]. From these considerable clinical evidences, the obviously close association between hypothyroidism and preeclampsia is established.…”
Section: Introductionmentioning
confidence: 99%